A compact multiband inverted a‐shaped patch antenna for WiMAX and C‐band. Issue 7 (July 2014) - Ahsan, Md Rezwanul; Islam, Mohammad T.; Ullah, M. Habib
ABSTRACT A compact modified inverted‐A shape multiband patch antenna has been designed and analyzed for worldwide interoperability for microwave access (WiMAX) and C‐band telecommunication satellite applications. The proposed antenna comprises of 20 × 20 mm2 radiating patch fed by 4‐mm long microstrip line on 1.6‐mm thick fiberglass polymer resin dielectric material substrate and a reduced ground plane. The proposed antenna has been designed and analyzed using market available widespread three dimensional high frequency electromagnetic simulator and measured in a standard far field anechoic chamber. The measurement result shows that impedance bandwidth (return loss < −10dB) 360 MHz (2.53–2.89 GHz) and 440 MHz (3.47–3.91 GHz) for WiMAX and 1550 MHz (6.28–7.83 GHz) for C‐band satellite applications. Maximum measured gain of 3.62, 3.67, and 5.7 dBi measured at lower, middle, and upper band, respectively. The measured almost stable radiation patterns and efficiencies have achieved from the proposed antenna in all bands of interest. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1540–1543, 2014